Using Citations to Generate Surveys of Scientific Paradigms - Mohammad, Saif; Dorr, Bonnie; Egan, Melissa; Awadallah, Ahmed; Muthukrishan, Pradeep; Qazvinian, Vahed; Radev, Dragomir; Zajic, David (NAACL '09 Proceedings of Human Language Technologies: The 2009 Annual Conference of the North American Chapter of the Association for Computational Linguistics, 2009)
The number of research publications in various disciplines is growing exponentially. Researchers and scientists are increasingly finding themselves in the position of having to quickly understand large amounts of technical material. In this paper we present the first steps in producing an automatically generated, readily consumable, technical survey. Specifically we explore the combination of citation information and summarization techniques. Even though prior work (Teufel et al., 2006) argues that citation text is unsuitable for summarization, we show that in the framework of multi-document survey creation, citation texts can play a crucial role.